2003
DOI: 10.1073/pnas.1534923100
|View full text |Cite
|
Sign up to set email alerts
|

Combined analysis of oligonucleotide microarray data from transgenic and knockout mice identifies direct SREBP target genes

Abstract: The synthesis of fatty acids and cholesterol, the building blocks of membranes, is regulated by three membrane-bound transcription factors: sterol regulatory element-binding proteins (SREBP)-1a, -1c, and -2. Their function in liver has been characterized in transgenic mice that overexpress each SREBP isoform and in mice that lack all three nuclear SREBPs as a result of gene knockout of SREBP cleavage-activating protein (SCAP), a protein required for nuclear localization of SREBPs. Here, we use oligonucleotide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

57
1,035
8
10

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 1,250 publications
(1,127 citation statements)
references
References 40 publications
57
1,035
8
10
Order By: Relevance
“…SREBP-2 is considered to be the global regulator of cholesterol synthesis (Horton et al, 2003) and is known to increase HMGCR transcripition (Sakakura et al, 2001). Our results are in contrast to a previous study where no difference between the two alleles was reported (Porcellini et al, 2007).…”
Section: Discussioncontrasting
confidence: 99%
“…SREBP-2 is considered to be the global regulator of cholesterol synthesis (Horton et al, 2003) and is known to increase HMGCR transcripition (Sakakura et al, 2001). Our results are in contrast to a previous study where no difference between the two alleles was reported (Porcellini et al, 2007).…”
Section: Discussioncontrasting
confidence: 99%
“…2F). Furthermore, SREBP_Direct_Hepatic_Target gene signature (Horton et al ., 2003), which is increased by in vivo overexpression of nuclear form SREBP‐1a (nSREBP‐1a) or nuclear form SREBP‐1 (nSREBP‐2), and decreased by in vivo SCAP knockout, was less enriched in cells with HDGF knockdown (Fig. 2G).…”
Section: Resultsmentioning
confidence: 99%
“…Gene sets were from msigdb _v6.1 (Broad Institute) and manually curated from studies (Horton et al ., 2003; Reed et al ., 2008; Rome et al ., 2008). Differentially expressed genes were rank‐ordered by fold change in expression.…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, SREBP1, that it is considered a global regulator of lipid synthesis (Eberlé et al, 2004), had a similar response to the ACC-α PIII transcripts in the mammary gland, whereas in adipose tissue had a similar response to ACC-α PI transcripts and FASN. SREBP1 regulates enzymes which synthesize FA and cholesterol from precursor molecules (Horton et al, 2003;Goldstein et al, 2006) and SREBP1 is a major regulator of mammary de novo FA synthesis and the response to dietary factors that modify milk fat in mouse (Anderson et al, 2007) and cow (Harvatine and Bauman, 2006).…”
Section: Discussionmentioning
confidence: 99%